Intraventricular Tension Pneumocephalus after Endoscopic Skull Base Surgery - Mammis, Antonios; Agarwal, Nitin; Eloy, Jean Anderson; Liu, James K. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
Background and Study Aims Postoperative pneumocephalus is commonly observed after neurosurgical intracranial procedures and is usually of little consequence. Intraventricular tension pneumocephalus, however, is a rare complication and a neurosurgical emergency that requires immediate intervention. We describe the first case of intraventricular tension pneumocephalus that developed 1 week following an expanded endoscopic endonasal approach for resection of a suprasellar mass.Patient A patient who underwent an endoscopic transplanum transtuberculum approach for resection of a suprasellar epidermoid tumor developed a sudden change in mental status, with imaging consistent with intraventricular tension pneumocephalus. Immediate endotracheal intubation and placement of an external ventricular drain prevented further deterioration. Endoscopic exploration of the skull base reconstruction revealed a one-way ball valve mechanism as the source of pneumocephalus. The skull base reconstruction was revised with autologous fascia lata and repositioning of the pedicled nasoseptal flap.Conclusion Intraventricular tension pneumocephalus is a rare neurosurgical emergency that may develop after endoscopic skull base surgery. Initial management includes endotracheal intubation and placement of an external ventricular drain to decompress the ventricles. Endoscopic exploration and revision of the skull base repair is imperative to obliterate the ball-valve fistula to prevent further entrapment of air.
Keywords: intraventricular tension pneumocephalus; endoscopic skull base surgery; endoscopic endonasal transplanum transtuberculum approach; suprasellar tumor; expanded endonasal approach